The Effect Of Marketing Mix On Consumer Decisions In Buying Chicken - Khusnul Mufid; Moh Kurdi (Cita Konsultindo Research Center, 2022)
Marketing is part of the main activities of traders to maintain the profitability of their business. The success and failure of business goals in marketing is influenced by other fields such as manufacturing, finance, and other fields. Mak Lut's shop, which is located in the Lenteng market, sells chicken meat from the morning until 5 pm every day. Mak Lut in carrying out its operations pays attention to several factors, namely in terms of maintaining the quality of chicken meat and prices. The population in this study were consumers at Kedai Mak Lut and the sample in this study was 75 samples using the accidental sampling. The analytical method used in this research is multiple linear analysis. The results of this study obtained (X1 Significant effect, (X2)price has a significant effect, (X3)location has a significant effect, (X4) promotion is not significant.